Ocular morbidity in the rural areas of Allahabad, India - Singh, A; Dwivedi, S; Dabral, SB; Bihari, V; Rastogi, AK; Kumar, D (Nepalese Journal of Ophthalmology, 2012)
Background: Although there has been a considerable reduction in the infective causes of ocular morbidity, the global burden of blindness has not significantly altered for over a decade. Objectives: To find the extent of ocular morbidity in different subgroups of the rural population and to study the factors associated with ocular morbidity. Materials and methods: A cross-sectional study was conducted at the Jasra and Saidabad blocks of Allahabad District. A total of eight villages were selected by multistage random sampling technique. The data were analyzed with SPSS Software. Results: Among 9,736 people surveyed, 931 cases of eye diseases were identified. Ocular morbidity was highest (40.92 %) among those aged above 60 years. A higher morbidity was also observed among females (53.60 %), illiterates (69.50 %) and those belonging to low socioeconomic strata (42.86 %). The main causes of ocular morbidity in the study population were cataract (41.89 %), uncorrected refractive errors (21.59 %), xerophthalmia (10.20 %) and glaucoma ( 4.83 %). Conclusions: Programs for cataract surgery, detection and treatment of glaucoma, correction of refractive errors and vitamin A prophylaxis for xerophthalmia need to be targeted to further reduce the burden of ocular morbidity. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5850 NEPJOPH 2012; 4(1): 49-53